امکان‌سنجی پیاده‌سازی الگوی تلفیقی اخلاق زیستی و هوشمندی راهبردی: از تئوری تا عمل - عباسپور احمد; امیرخانی امیرحسین; پورعزت علی‌اصغر; حضوری محمدجواد (مجله اخلاق زیستی- علمی پژوهشی, 2020)
Background and Aim: Organizations need reliable and robust strategies to survive and thrive in an unstable environment. Many authors believe that knowledge is the most important input to the process of strategy formulation, implementation and evaluation. As such, it is important to know how to collect, analyze and process the knowledge required. The purpose of this paper is to design a strategic intelligence process model at the organizational analysis level. Materials and Methods: The textual data of this study were collected in English and Persian through the databases of EBSCO, Google Scholar and Iran Doc. Findings: The findings of the study showed that the process of strategic intelligence for the experts in the state banking industry consists of eight stages. The two stages of "need determination" and "planning and organization" are process drivers, which through the "information gathering" phase lead to the following steps: "Purifying and storing useful information", "information analysis", "production Intelligence", "Distributing Intelligence and Ethics" and "Using Intelligence and Feedback". Conclusion: The results of this study provide insights into the implementation of the strategic intelligence process in organizations and evaluate its effectiveness. Because decision-making patterns follow value systems, these value systems give different ratings to different decisions and when referring to the system when a person, or social organization, faces multiple decisions at the same time. Governing value selects decisions that, overall, gain a higher rank in the accepted value system and those are decisions that ensure the utility of the individual or the social system. Therefore, mere review of policies, plans and operational plans (strategic levels) in strategic environmental assessment will not suffice in terms of their compliance with environmental criteria, as they may at some stage need to "formulate" the plan and its implementation is made; irreversible decisions are made that require a lot of costs to reform. Please cite this article as: Abbaspour A, AmirKhani AH, Pourezzat AA, Hozoori MJ. Feasibility of Implementing the Integrated Model of Biological Ethics and Strategic Intelligence: From Theory to Practice. Bioethics Journal, Special Issue on Bioethics and Citizenship Rights 2020; 81-103.